LIFESTYLE AND AUTOIMMUNITY: HOW MODERN HABITS SHAPE IMMUNE DYSREGULATION - Aleksandra Tomaszewska; Kinga Karczewska; Michalina Chodór; Maciej Kokoszka; Natalia Dymel; Ryszard Feret; Sonia Mojzyk; Aleksandra Mierniczek; Aleksandra Ćwirko-Godycka; Nikola Murawska (International Journal of Innovative Technologies in Social Science, 2025)
According to current estimates, between 80 and 150 autoimmune diseases have been identified. In the United States alone, over 50 million individuals live with an autoimmune condition. These disorders substantially impact healthcare expenditures and, most importantly, the quality of life, mental health, and physical functioning of affected patients. Epidemiological data indicate a steady increase in both the incidence and recognition of autoimmune diseases. Modern lifestyle factors exert a profound influence on immune system function and may contribute to their development. This review discusses key everyday habits—such as stress, physical activity, the use of substances (alcohol consumption, smoking), contemporary dietary patterns, the growing epidemic of obesity, sleep, as well as infections with pathogens such as SARS-CoV-2—that modulate immune responses and promote their dysregulation. This article is a comprehensive review based on studies retrieved from scientific databases such as PubMed and Google Scholar, with sources selected for their relevance and significance to the topic. The analysis indicates that chronic stress, sleep deprivation, substance use, and highly processed diets exacerbate inflammatory processes, immunosenescence, and inflammaging, thereby increasing susceptibility to autoimmunity. Conversely, health-promoting non-pharmacological interventions—including lifestyle modification, stress-regulation techniques, and regular physical activity—may alleviate immunological disturbances and improve patients’ functioning and quality of life. In light of current evidence, an integrated approach that combines medical treatment with lifestyle interventions represents a key component of both the prevention and management of autoimmune disorders.